2013
DOI: 10.1016/j.breast.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Does immediate breast reconstruction compromise the delivery of adjuvant chemotherapy?

Abstract: We found no evidence that IBR compromised the delivery of adjuvant chemotherapy, although there was a significant incidence of implant infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
12
0
2
Order By: Relevance
“…Recently, a prospective study of US-elastography techniques showed similar overall diagnostic performance in the differentiation of benign from malignant lesions and, when combined with B-mode US, led to improved diagnostic performance. Barr has reported that the addition of qualitative measurements to SWE can improve the accuracy of SWE so that it comes close to that of SE [21,22].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a prospective study of US-elastography techniques showed similar overall diagnostic performance in the differentiation of benign from malignant lesions and, when combined with B-mode US, led to improved diagnostic performance. Barr has reported that the addition of qualitative measurements to SWE can improve the accuracy of SWE so that it comes close to that of SE [21,22].…”
Section: Discussionmentioning
confidence: 98%
“…A mastectomia + IBR szövődményaránya általában magasabb, mint az SM-é, de a legtöbb közlés szerint az adjuváns kezelés "hátráltatása" átlagosan napokban mér-hető, nem szignifikáns vagy szignifikáns, de mégsem bír klinikai jelentőséggel [18][19][20]22]. Jelen vizsgálatunkban…”
Section: Megbeszélésunclassified
“…Der Eingriff ist prinzipiell in jedem Alter möglich [4] 10% der primär implantierten Prothesen mussten in dem berichteten Studienkollektiv entfernt werden [6].…”
Section: Einsatz Von Implantatenunclassified